Disparities in HIV treatment and physician attitudes about delaying protease inhibitors for nonadherent patients. - Wong, Mitchell D; Cunningham, William E; Shapiro, Martin F; Andersen, Ronald M; Cleary, Paul D; Duan, Naihua; Liu, Hong Hu; Wilson, Ira B; Landon, Bruce E; Wenger, Neil S (Journal of general internal medicine, 2004)
Current HIV treatment guidelines recommend delaying antiretroviral therapy for nonadherent patients, which some fear may disproportionately affect certain populations and contribute to disparities in care.
Keywords: Adult; Attitude of Health Personnel; Female; Health Status; Hispanic Americans; HIV Infections; Humans; Income; Male; Multivariate Analysis; Physician's Practice Patterns; Prospective Studies; Protease Inhibitors; Treatment Outcome; Treatment Refusal